Numerical/Experimental Study of the Impact and Compression after Impact on GFRP Composite for Wind/Marine Applications. (2016) - Perillo, G.; Jørgensen, J.K.
Abstract: Damage development due to impact needs to be understood to evaluate the consequences of impact on composite structures. This study concentrates on modelling low velocity impact and consequent compression after impact (CAI) test on thick industrial composites made from glass fiber epoxy produced by vacuum assisted resin infusion. Cross-plied laminates were tested with different impact energies and different numbers of interfaces (clustering). Results were compared to a 3D finite element analysis. Interfaces and their damage development were modelled with cohesive elements. Intraply properties were modelled by progressive failure analysis. The results show that the numerical model using only simple and independently measured material data was able to predict the impact and CAI behavior for the different energies and different stacking sequences.